PENERAPAN AKUNTANSI ISLAM DAN PELAPORAN CORPORATE SOCIAL RESPONSIBILITY PERBANKAN SYARIAH - Wahyuni, Mirasanti (PRESTASI, 2013)
Abstract   This research is descriptive analysis. The study was conducted by comparing the execution and reporting of Corporate Social Responsibility Islamic bank with items sharia-compliant reporting enterprise theory. The study was conducted by analyzing secondary data from annual reports Bank Mandiri Syariah and Bank Muamalat in 2012. The result is the Bank Syariah Mandiri is still not in accordance with the Syariah concept of Enterprise Theory (SET), especially in the horizontal accountability of nature. This means that the Bank Syariah Mandiri is still the least disclosure of CSR on the environment. Bank Muamalat has been quite a lot of items in the draft implementing Sharia Enterprise Theory. Implementation was not centered on a large provincial town or certain activities which are still lacking in the items that must be disclosed is in an effort to improve both spiritual education to the surrounding community as well as for employees when the item includes an important item category.  Keyword : Syariah enterprise theory, Corporate Social Responsibility